Synergistic role of acid sites in the Ce-enhanced activity of mesoporous Ce-Al-MCM-41 catalysts in alkylation reactions: FTIR and TPD-ammonia studies - Kalita, Pranjal; Gupta, Narendra M.; Kumar, Rajiv (Journal of Catalysis, 2007)
The acidic properties of Ce-x-Al-y-MCM-41 with different Ce/Al/Si atomic ratios were examined by pyridine-FTIR and ammonia-TPD methods. Both the density and the strength of the acid sites were considerably higher in the samples containing both Ce and Al than in the samples with only one of these substituents. The IR spectra of chemisorbed pyridine revealed that the Ce-Al-MCM-41 samples contained at least two distinct Lewis acid sites, L-2 (1595-1444 cm(-1)) and L-1 (1613-1452 cm(-1)), where the L-2/L-1 ratio increased progressively with increasing Ce/Al atomic ratio in a series of samples with similar Si/Al ratios. In addition, the density of the Bronsted acid sites (B) as well as the B/L-1 ratio increased with increasing Ce/Al molar ratio in these samples. The findings of this study help us understand the synergistic role played by Lewis and Bronsted acid sites in the catalytic activity of these catalysts for the benzylation of toluene. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

Structure sensitivity of nano-structured CdS/SBA-15 containing Au and PtCo-catalysts for the photocatalytic splitting of water - Lunawat, Puja S.; Kumar, Rajiv; Gupta, Narendra M. (Catalysis Letters, 2008)
Photocatalysts containing nanocrystallites of cadmium sulphide dispersed in the channels of mesoporous silicate SBA-15 exhibited enhanced activity for visible-light mediated splitting of water, as compared to bulk CdS. Whereas the incorporation of 1 wt.% Pt co-catalyst in CdS/SBA-15 led to a substantial increase in H-2 yield, Au at similar loading resulted in marginally decreased activity. The results indicate that the photocatalytic activity of CdS crystallites is structure sensitive. Similarly, the role of a noble metal may be associated with the particle size dependent micro-structural features, rather than its electronic properties such as the work function or the heat of adsorption of reactant or product molecules.
Keywords: nano-structured cadmium sulphide; Photocatalysis; role of noble metal co-catalyst; Splitting of water; structure sensitivity

Synthesis, characterization and catalytic performance of Sn-MCM-48 in solvent-free Mukaiyama-type aldol condensation reactions - Taralkar, U. S.; Kalita, Pranjal; Kumar, Rajiv; Joshi, P. N. (Applied Catalysis A-General, 2009)
The influence of various synthesis variables on the physico-chemical properties of mesoporous stannosilicate molecular sieves with MCM-48 structure (Sn-MCM-48) has been investigated. Sn-MCM48 has been used as a new heterogeneous catalyst in solvent-free Mukaiyama-type aldol reactions. Invariably, the beta-hydroxy ester selectivity was found to be 100% irrespective of the conversion level. The product yield was found to increase, to reach a maximum (70%), and then to decrease with the increase in tin content. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Characterization; heterogeneous catalysis; Hydrothermal synthesis; Mesoporous molecular sieves; Mukaiyama-aldol condensation; Sn-MCM-48

Solvent-free mukaiyama-aldol condensation catalyzed by Ce-Al-MCM-41 mesoporous materials - Kalita, Pranjal; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2011)
MCM-41 samples containing Ce4+ and Al3+ in the network, designated as Ce-x-Al-MCM-41 (x = 0.0-0.04), were synthesized and characterized systematically. These samples exhibited higher catalytic activity for Mukaiyama-aldol condensations to produce beta-hydroxy carbonyl compounds under the solvent free conditions, compared to the samples containing either of the two cations. The product yield was found to depend on the electron donating/withdrawing characteristics of reactant molecules being responsible for the observed trend. Series of solvents were also investigated but considerably high yield of aldol products (similar to 95%) could be achieved without using any solvents. In all the cases, the selectivity was found to be 100%, typical of such Mukaiyama-aldol condensations. The higher catalytic activity of Ce-x-Al-MCM-41 is explained on the basis of certain new acid sites generated due to co-incorporation of Ce and Al cations. Published by Elsevier Inc.
16th IZC/7th IMMS Conference, Sorrento, ITALY, JUL 04-09, 2010
Keywords: Acid catalyst; Ce-Al-MCM-41; Silyl enol ether and aldehyde; Silyl ketene acetal

Solvent-free coumarin synthesis via pechmann reaction using solid catalysts - Kalita, Pranjal; Kumar, Rajiv (Microporous and Mesoporous Materials, 2012)
A solvent-free versatile and efficient methodology, reported here, allows the synthesis of coumarin by hydroxyalkylation of phenols with ethyl or methyl acetoacetate (via Pechmann reaction) using trifluoromethanesulfonic acid (trifle acid) functionalised Zr-TMS (Zr-TMS, zirconia based transition metal oxide mesoporous molecular sieves) catalysts with different loadings of triflic acid over Zr-TMS (5-25 wt.%) where the total acid strength of acid functionalised Zr-TMS material is increased as increasing loading of triflic acid from 5 to 25 wt.% leading to correspond increased higher catalytic activity. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Coumarin; Ethyl acetoacetate; Functionalization; Pechmann reaction; Resorcinol; Zr-TMS